Studi Evaluasi Satuan Kurikulum Pendidikan Non Formal Di PKBM Yayasan Quantum Indonesia - Junaidi Junaidi; Rahmat Rahmat; Sri Wahyuni Tanshzil (SAP (Susunan Artikel Pendidikan), 2026)
Non-formal education plays a strategic role in expanding access to education, but its curriculum implementation in PKBM still faces challenges related to suitability with students' needs and adaptation to the Merdeka Curriculum policy. This study aims to evaluate the non-formal education curriculum unit at the PKBM Yayasan Lingkaran Quantum Indonesia in Denai Lama Village to assess the alignment of curriculum planning, implementation, and evaluation with the local context and national education policy. The research method uses a qualitative method with a descriptive approach with data collection through interviews, observation, and documentation with a research period of 1 month from November to December 2025. As well as data analysis using data reduction, data display, and data verification. The results of the study indicate that the non-formal education curriculum unit at the PKBM Yayasan Lingkaran Quantum Indonesia in Denai Lama Village has been designed and implemented adaptively, contextually, and in line with the principles of non-formal education and the Merdeka Curriculum policy. The curriculum structure that integrates intracurricular, co-curricular, and extracurricular activities has been proven to support the strengthening of academic competencies, life skills, and the values ​​of the Pancasila Student Profile. The implementation of deep learning through a mindful, meaningful, and joyful learning approach, supported by various active learning models, increases student engagement and the quality of the learning experience. Furthermore, a holistic assessment system based on assessment for learning, assessment as learning, and assessment of learning allows for comprehensive and continuous monitoring of student progress.